Gastrointestinal parasites in captive wild animals from two Brazilian Zoological Gardens (Research, Society and Development, 2022)
Keeping animals in zoos is important for the preservation of endangered species. However, captive animals can also be affected by different species of parasites. Herein, we aimed to evaluate the occurrence of gastrointestinal parasites in wild and exotic animals from two zoos in the state of Sergipe, Northeastern Brazil.  Fecal samples were obtained by spontaneous defecation of 287 specimens, grouped into mammals (n = 101), birds (n = 99), and reptiles (n = 87). The samples were assessed using two techniques, Mini-FLOTAC and Ziehl-Neelsen, to identify helminths and protozoa, respectively. In total, 60.2% (173/287) of the animals evaluated were positive for some type of gastrointestinal parasite. Among the classes evaluated, mammals (81.1%; 82/101; p-value